Paradoxical and Retrograde Air Embolism from Pressurized Peripheral Bolus - Joshua Santucci; Naresh Mullaguri; Anusha Battineni; Raviteja R. Guddeti; Christopher R. Newey (Case Reports in Neurological Medicine)
Introduction. Cerebral air embolism is a rare, yet serious neurological occurrence with unclear incidence and prevalence. Here, we present a case of fatal cerebral arterial and venous cerebral gas embolism in a patient with infective endocarditis and known large right-to-left shunt and severe tricuspid regurgitation following pressurized fluid bolus administration. Case Presentation. A 32-year-old female was admitted to the medical intensive care unit from a long-term acute care facility with acute on chronic respiratory failure. Her medical history was significant for intravenous heroin and cocaine abuse, methicillin-sensitive Staphylococcus aureus tricuspid valve infective endocarditis on vancomycin, patent foramen ovale, septic pulmonary embolism with cavitation, tracheostomy with chronic ventilator dependence, multifocal cerebral infarction, hepatitis C, nephrolithiasis, anxiety, and depression. After intravenous fluid administration, she became unresponsive with roving gaze, sluggish pupils, and hypotensive requiring vasopressors. CT of the brain showed diffuse arterial and venous cerebral air embolism secondary to accidental air administration from fluid bolus. Magnetic resonance imaging of the brain showed diffuse global anoxic injury and flattening of the globe at the optic nerve insertion. Given poor prognosis, her family chose comfort measures and she died. Conclusions. Fatal cerebral air embolism can occur through peripheral intravenous routes when the lines are inadequately primed and fluids administered with pressure. Caution must be exercised in patients with right-to-left shunting as air may gain access to systemic circulation.